2017
DOI: 10.1016/bs.ctm.2016.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Mechanosensitive Piezo Channels in the Gastrointestinal Tract

Abstract: Sensation of mechanical forces is critical for normal function of the gastrointestinal (GI) tract and abnormalities in mechanosensation are linked to GI pathologies. In the GI tract there are several mechanosensitive cell types—epithelial enterochromaffin cells, intrinsic and extrinsic enteric neurons, smooth muscle cells and interstitial cells of Cajal. These cells use mechanosensitive ion channels that respond to mechanical forces by altering transmembrane ionic currents in a process called mechanoelectrical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
58
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(59 citation statements)
references
References 151 publications
(177 reference statements)
1
58
0
Order By: Relevance
“…5b), suggesting they have the capacity to directly sense distention. Previous studies reported Piezo1 expression in the ENS (78,79), which our atlas allows us to map to specific subsets. This refinement raises the hypothesis that peristalsis is at least partially driven by distention, specifically via motor neuron depolarization through Piezo1.…”
Section: Motor Neuron Expression Profiles Suggest That Mechanosensatimentioning
confidence: 81%
“…5b), suggesting they have the capacity to directly sense distention. Previous studies reported Piezo1 expression in the ENS (78,79), which our atlas allows us to map to specific subsets. This refinement raises the hypothesis that peristalsis is at least partially driven by distention, specifically via motor neuron depolarization through Piezo1.…”
Section: Motor Neuron Expression Profiles Suggest That Mechanosensatimentioning
confidence: 81%
“…This indicates that duodenal sensitivity to distension‐induced contraction in rabbits on long‐term low‐fiber diet decreased. It is well known that the gastrointestinal tract contains intrinsic and extrinsic enteric neurons, smooth muscle cells, and interstitial cells of Cajal (ICC), which respond to mechanical deformations by altering transmembrane ionic currents in a process called mechanoelectrical coupling . It has been demonstrated that factors such as aging and diabetes change the mechanosensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…To encode for such wide‐ranging stimuli, visceral organs rely on an array of stimuli‐activated primary ‘sentinel’ transducers, including transient receptor potential (TRP) channels, acid‐sensing ion channels (ASIC), mechanosensitive two‐pore domain K (K2P) channels and Piezo channels (Grundy, ; Brierley, ; Christianson & Davis, ; La & Gebhart, ; Brierley, ; Alcaino et al . ). Furthermore, primary transducers and ion channels involved in sensory signalling can be modulated and controlled by G‐protein coupled receptors (GPCRs) and regulators of GPCR signalling proteins, in response to endogenous mediators (Geppetti et al .…”
Section: Introductionmentioning
confidence: 97%